2015
DOI: 10.1111/gcb.13088
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term elevated air [CO2] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species

Abstract: The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [CO2 ] and temperature in cultivated genotypes of Coffea arabica L. (cv. Icatu and IPR108) and Coffea canephora cv. Conilon CL153. Plants were grown for ca. 10 months at 25/20°C (day/night) and 380 or 700 μl CO2 l(-1) and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
224
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(258 citation statements)
references
References 57 publications
30
224
0
4
Order By: Relevance
“…Such preservation of adequate mineral contents and balance within the plant is determinant for the expression of stress tolerance mechanisms on coffee (Ramalho et al, 2013), and assume a particular importance under predicted future conditions of climate changes and global warming (Martins et al, 2014), which are expected to simultaneously alter temperature and water availability to main crops, including to coffee (Rodrigues et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Such preservation of adequate mineral contents and balance within the plant is determinant for the expression of stress tolerance mechanisms on coffee (Ramalho et al, 2013), and assume a particular importance under predicted future conditions of climate changes and global warming (Martins et al, 2014), which are expected to simultaneously alter temperature and water availability to main crops, including to coffee (Rodrigues et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…They also demonstrated a relevant heat resilience of coffee species and showed that an elevated CO 2 concentration remarkably mitigated the impact of heat on coffee physiology. In this regard, and fortunately, future perspectives on the sustainability of the coffee crop that are based on increasing temperature scenarios should not be as catastrophic as previously predicted (Rodrigues et al, 2016). …”
Section: Introductionmentioning
confidence: 89%
“…By studying the physiological and biochemical responses of photosynthesis to elevated atmospheric CO 2 concentration and/or temperature in several C. arabica and C. canephora genotypes, Rodrigues et al (2016) demonstrated that predictions concerning the impacts of climate change and global warming should consider the role of CO 2 as a key player in coffee heat tolerance. They also demonstrated a relevant heat resilience of coffee species and showed that an elevated CO 2 concentration remarkably mitigated the impact of heat on coffee physiology.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bunn et al (2015), higher temperatures may imply reduction in area suitable for coffee production. However, Rodrigues et al (2016) evaluating the interaction of high temperature coupled with the increase of CO 2 concentration on Coffea canephora and Coffea arabica, found increasing CO 2 concentrations strongly mitigated the effects of high temperatures on the photosynthetic machinery of coffee plants. In what concerns the relative humidity levels (RH), the Australian cedar promoted higher values along the entire year on both distances (T1 and T2) when compared to T3 (Fig.…”
Section: Figmentioning
confidence: 99%